Protective roles of the red-dragon fruit peels (Hylocereus costaricensis) against the cigarette-smoke harmful effect in Wistar rats - Ardhianditto, Decca; Murwani, Retno; Johan, Andrew; Ariyanto, Diaza Okadimar (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2023)
Background:  Many people are exposed to cigarette smoke unintentionally in numerous places worldwide. Cigarette smoke contains carbon monoxide, nicotine, and polycyclic aromatic hydrocarbons, which are toxic and can trigger the production of free radicals in the body.Objective: To study the impact of cigarette-smoke exposure twice daily for 30 days on 4-5 weeks Rattus norvegicus L. without or with a daily intake of the juice or ethanol extract of the red-dragon fruit peels H. costaricensis.  Materials and Methods: Twenty-eight 4-5 weeks old male Wistar rats were randomly allocated into Control (not exposed to cigarette-smoke), exposed to cigarette-smoke only (Csmoke), exposed to cigarette-smoke and H. Costaricensis-peel juice (JcHc), exposed to cigarette-smoke and had H. Costaricensis-peel extract (ExHc). Cigarette-smoke exposure was given twice daily. The juice (3g/mL) and extract (3.15g/mL) were given for 30 days ad libitum. Feed and drink intake, body weight, and serum biochemistry (MDA, bilirubin, ALT and AST) were determined. Data were analyzed by ANOVA.Results: The positive control group with cigarette-smoke exposure (Csmoke) had a significant elevation in serum malondialdehyde (MDA), alanine-transaminase (ALT), and aspartate-transaminase (AST) and drinking water intake (p<0.05) but reduced feed intake and body weight (p<0.05). The JcHc and ExHc groups had reduced serum MDA, ALT, and AST and higher body weight and feed intake than the Csmoke, and the extract had a better reduction than the juice (p<0.05). Furthermore, the extract had a lower biochemical profile than the Control group (p<0.05).Conclusion: The disturbance in serum MDA, ALT, AST, water and feed intake, and body weight by cigarette smoke was ameliorated by H. costaricensis peel juice or extract daily for 30 days. H. costaricensis peel juice or extract can be used to prevent the adverse effects of cigarette smoke exposure and has the potential to be developed into valuable products.